Multiple‐antenna phase‐gradient detection for OAM radio communications. Issue 9 (1st April 2015) - Cano, E.; Allen, B.
Abstract : Two new multiple‐antenna phase‐gradient detection schemes for orbital angular momentum (OAM) communication systems are presented. Their bit error rate performances are obtained by means of Monte Carlo simulations. Results show that their performance is highly dependent on the circular separation among the receiver antennas. The paired‐antenna phase‐gradient receiver outperforms the uniformly spaced antenna receiver when a large number of antennas are used.